Enhanced simultaneous removal of Cr(vi) and Cd(ii) from aqueous solution and soil: a novel carbon microsphere–calcium alginate supported sulfide-modified nZVI composite. Issue 9 (3rd August 2022) - Liang, Weiyu; Shen, Yihao; Xu, Chen; Cai, Dongqing; Wang, Dongfang; Luo, Kailun; Shao, Xuechun; Qiao, Zhihua; Zhang, Wei; Peng, Cheng
Abstract : Industrial production activities commonly lead to excessive hexavalent chromium [Cr(vi )] and cadmium [Cd(ii )] release to water and soil, which significantly endanger the ecological environment and human health. Abstract : Industrial production activities commonly lead to excessive hexavalent chromium [Cr(vi )] and cadmium [Cd(ii )] release to water and soil, which significantly endanger the ecological environment and human health. In this study, a novel calcium alginate doped with renewable biomass carbon microsphere-supported sulfide-modified nZVI bio-based ternary composite (S-nZVI@CMS@CA) was prepared to remove Cr(vi ) and Cd(ii ) simultaneously in water and soil. The results revealed that CMS@CA greatly improved the stability and provided more active adsorption sites for heavy metals, and sulfide modification effectively enhanced the reactivity of nZVI. The adsorption capacities of Cr and Cd(ii ) were 2.913 mg g −1 and 4.527 mg g −1 after 1 h of reaction, respectively. Cations (Mg 2+ and Ca 2+ ) promoted the adsorption of Cr(vi ) and Cd(ii ), while anions (H2 PO4 −, SO4 2−, and Cl − ) and humic acid inhibited the adsorption. Meanwhile, the removal efficiencies of Cr and Cd(ii ) in natural lake water were higher than those in ultrapure water and tap water. SEM-EDS, FTIR and XPS analysis results showed that the mechanisms of Cr(vi ) removal were redox and electron transfer under the combined action of iron–carbon microelectrolysis, and that of Cd(ii ) removal were chemical precipitation and surface complexation. The practicality of S-nZVI@CMS@CA was further verified by the remediation of Cr and Cd polymetallic contaminated soil. These results provide new insights into developing an effective solution for removing Cr and Cd simultaneously from water and soil.